2021
DOI: 10.1130/g49429.1
|View full text |Cite
|
Sign up to set email alerts
|

The influence of off-fault deformation zones on the near-fault distribution of coseismic landslides

Abstract: Coseismic landslides are observed in higher concentrations around surface-rupturing faults. This observation has been attributed to a combination of stronger ground motions and increased rock mass damage closer to faults. Past work has shown it is difficult to separate the influences of rock mass damage from strong ground motions on landslide occurrence. We measured coseismic off-fault deformation (OFD) zone widths (treating them as a proxy for areas of more intense rock mass damage) using high-resolution, thr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 31 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…This being said, there is still some ambiguity as to the influence of rock mass deformation from fault zones along the coast that did not rupture significantly in 2016; for example, the Hope fault which extends just offshore in parallel to much of the north Kaikōura coast. A history of strong ground motion and fault deformation has been shown to progressively decrease rock mass strength and increase landslide susceptibility over multiple earthquakes (Parker et al, 2015;Gischig et al, 2016;Bloom et al, 2022a;Massey et al, 2022). This may result in an increased landslide susceptibility due to amplification of strong ground motion and decreased rock mass strength.…”
Section: Factors Controlling Increased Coastal Landslide Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…This being said, there is still some ambiguity as to the influence of rock mass deformation from fault zones along the coast that did not rupture significantly in 2016; for example, the Hope fault which extends just offshore in parallel to much of the north Kaikōura coast. A history of strong ground motion and fault deformation has been shown to progressively decrease rock mass strength and increase landslide susceptibility over multiple earthquakes (Parker et al, 2015;Gischig et al, 2016;Bloom et al, 2022a;Massey et al, 2022). This may result in an increased landslide susceptibility due to amplification of strong ground motion and decreased rock mass strength.…”
Section: Factors Controlling Increased Coastal Landslide Densitymentioning
confidence: 99%
“…The earthquake ruptured faults of both the North Canterbury and the Marlborough Fault System tectonic domains (Figure 1, Litchfield et al, 2018) and caused complex surface deformation along c. 110 km of coastline (Clark et al, 2017). The earthquake generated more than 30,000 landslides which were primarily concentrated within the steep slopes of the Seaward Kaikōura range, around surface fault ruptures, and in steep sections of coastline (Figure 1 and 2; Massey et al, 2018Massey et al, , 2020aBloom et al, 2022a). Statistical modelling by Massey et al (2018Massey et al ( , 2020a found that the regional distribution of landslides from the Kaikōura earthquake was well explained by geology, slope, distance to surface fault traces, peak ground velocity (PGV), local slope relief, and elevation.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of rock mass damage along with the absence of healed (i.e., veined or cemented) joints observed in the borehole furthermore suggest that healing processes at this site do not play a significant role over the time periods between strong ground-shaking events (approximately every few hundred years at this site). Furthermore, past coastal erosion has likely steepened the Half Moon Bay site and contributed to landslide development (Bloom et al, 2023).…”
Section: Landslide Failure Complex Evolutionmentioning
confidence: 99%
“…2A ) ( 14 ). Oblique left-lateral reverse displacement produced some of the largest offsets recorded in the Kaikōura event ( 31 , 33 ), with the Papatea fault scarp displacing the Waiau Toa/Clarence River in four locations in an area referred to as Priam’s flat ( Fig. 2B ).…”
Section: Introductionmentioning
confidence: 99%
“…Excellent pre- and post-event data covering the Papatea fault rupture and associated avulsion provided an opportunity to analyze FIRA variables in more detail. Landscape change was captured through multitemporal lidar and allowed us to measure high-resolution near-field displacements ( 33 , 34 ). River discharge of 187 m 3 s −1 was recorded by an Environment Canterbury gauge attached to Glen Alton Bridge ( Fig.…”
Section: Introductionmentioning
confidence: 99%